Pattern of Homicidal Deaths at Raichur District Region – A Retrospective Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: It is a retrospective study carried out to find out the pattern of homicidal deaths in around the Raichur district region, among autopsies conducted at mortuary, RIMS, Raichur. Materials and Methods: This is a two year retrospective study of autopsies conducted from January 2016 to December 2017 at Raichur Institute of Medical Sciences, Raichur. The objectives of the study were to know the pattern of homicidal deaths in and around Raichur district and to study the various socio-demographic factors influencing the homicidal deaths. Using a predefined and structured Performa, all the necessary details pertaining to the cases were collected from the inquest report and were analyzed. Results: There were 757 total cases of autopsies conducted during the study period, of which there were 51 (6.73%) homicidal deaths. Male preponderance, 20-29 age group, blunt weapons - most commonly used, neck - commonest region of body involved constitutes 29.52%, most common cause of death - hemorrhage and shock 25.49%( 13) equally followed by Head injury, maximum homicide took place at the victim‘s residence (58.82%), the most common motive behind the homicide was Infidelity (21.56%), maximum numbers of homicides were committed by Spouse (27.45%). Conclusion: An attempt is made to know the socio demographic profile of the deceased so as to understand the sociological, economical, demographic and psychological aspects influencing homicidal deaths. The spurt in the homicidal deaths in our region may be attributed to the poor socio – economic condition, unemployment among young people, marital and family disputes, decreasing value based morality in the society, soft and sometimes toothless law enforcement agencies. Key